The Effect Of Exercises As Standardized Resistance On The Improvement Of Abdomen and Arm Muscles According to Motor Pathway and Some Kinematical variables In Young Pole Vaulting Achievement - Mohammed, Addel (Journal of Physical Education, 2017)
The importance of the research lies in using exercises as standardized resistanceto improve important arms and abdomen muscles that help the vaulter complete the correcttechnique and for better achievement. The problem of the research lies in vaulters incompletearm extension during placing and pushing the pole before passing the bar as well as bodyextension before passing the bar and the early release of the pole causing the vaulter to touchand the bar. The research aimed at designing exercises as standardized resistance forimproving abdomen and arm muscles according to motor pathway. In addition to that theresearcher aimed at identifying the effect of these exercises as standardized resistance forimproving abdomen and arm muscles according to motor pathway of young pole vaulters aswell as identifying the effect of these exercises as standardized resistance on somekinematical variables and young pole vault achievement. The researcher hypothesizedstatistical difference between pre and posttests in arms' and abdomen special strength as wellas kinematical variables of pole vaulters in favor of posttests. The researcher used theexperimental method. The subjects were (10) pole vaulters. The data was collected andtreated using proper statistical operations. The researcher concluded that the exercises usedby the experimental group improved strength faster than the exercises used by the controllinggroup. In addition to that, the researcher concluded increasing resistance increases thevaulter's strength. Finally he recommended using varied exercises to improve specialstrength as well as the necessity of using standard resistance to improve strength andachievemen